An investigation to assess the potential of CD25highCD4+ T cells to regulate responses to donor alloantigens in clinically stable renal transplant recipients. - Akl, A; Jones, N; Rogers, N; Bakr, M; Mostafa, A; El Shehawy, E; Ghoneim, M; Wood, K (2008)
Regulatory T cells are enriched within CD25(high)CD4(+) leukocytes, however their role in renal transplant recipients with stable function vs. recipients with biopsy-proven chronic allograft dysfunction remains unclear. We therefore studied the number, phenotype, and function of CD25(high)CD4(+) cells in the peripheral blood of 30 renal transplant recipients of living-related grafts, comprising 15 rejection-free recipients with stable graft function (Group A) and 15 with biopsy-proven chronic graft dysfunction (Group B). A higher absolute number of CD25(high)CD4(+) cells were present in the peripheral blood of rejection-free recipients (Group A) vs. those recipients with chronic graft dysfunction (Group B) (P = 0.019); but there was no significant difference with healthy volunteers (P = 0.084). In carboxyfluorescein diacetate succinimidyl ester-mixed leukocyte culture assays, depletion of CD25(high)CD4(+) revealed active regulation in 11 (74%) of 15 rejection-free recipient samples (Group A) in response to donor- but not third party-leukocytes, whereas no regulatory activity was observed in any samples from recipients with chronic graft dysfunction (Group B). In conclusion, these data provide evidence for the presence of an increased number of CD25(high)CD4(+) T cells with donor-specific regulatory activity in the peripheral blood of renal transplant recipients with stable graft function compared with recipients with chronic graft dysfunction.